Effectiveness of Mindfulness-Based Cognitive Therapy on Perceived Social Support and Resilience in Individuals with Morbid Obesity - Sharifi Nouri, Sima; Abdivarmazan, Morad (KMAN Counseling & Psychology Nexus, 2026)
The objective of the present study was to examine the effectiveness of mindfulness-based cognitive therapy on perceived social support and resilience in individuals with morbid obesity. The research employed a quasi-experimental method with a pretest–posttest control group design. The statistical population consisted of individuals with morbid obesity (BMI above 40) residing in District 8 of Tehran in 2025, from which 30 individuals were selected through purposive sampling and randomly assigned to experimental and control groups (15 participants in each group). Mindfulness-based cognitive therapy was administered to the experimental group in eight sessions, each lasting 90 minutes, while the control group received no intervention. Data were collected using the Multidimensional Scale of Perceived Social Support (Zimet et al., 1988) and the Connor-Davidson Resilience Scale (Connor & Davidson, 2003). The mindfulness-based cognitive therapy protocol was delivered in eight weekly group sessions of 90 minutes each. Data analysis was performed using multivariate analysis of covariance. The findings indicated that, after controlling for the pretest effect, there was a statistically significant difference at the 0.05 level between the experimental and control groups in posttest scores of perceived social support and resilience. Therefore, mindfulness-based cognitive therapy can be considered an effective intervention for individuals with morbid obesity.